FEASIBILITY ANALYSIS OF DESCRIPTION TEXT TEACHING MATERIALS HELPED BY LUMI EDUCATION IN CLASS VII SMP - Frederika Marbun; Mara Untung Ritonga; Wisman Hadi (Curricula: Journal of Teaching and Learning, 2024)
This study aims to evaluate the appropriateness of open-text material descriptions in aiding Lumi's education for class VII students at SMP Negeri 2 Tanjungbalai. This research follows a Research and Development (R&D) approach using the ADDIE model, which includes analysis, design, development, implementation, and evaluation phases. The internal data sources for this study comprise 32 class VII students and an Indonesian language teacher at SMP Negeri 2 Tanjungbalai. Data collection methods include observations, interviews, documentation, questionnaires, and student test results. Instruments used for evaluating the open text material's appropriateness include product validation questionnaires for material experts, design experts, teacher responses, student responses, and pre-test and post-test assessments for students. The results indicate that the material validation by experts yielded an appropriateness percentage of 84.64%, categorized as "Very Worthy." The design expert validation showed an appropriateness percentage of 90.73%, also rated as "Very Worthy." Teacher responses resulted in an appropriateness percentage of 83.2%, classified as "Very Worthy," while student responses indicated an appropriateness percentage of 92.92%, similarly categorized as "Very Worthy." These findings suggest that open-text materials are highly suitable for educational purposes in this context.